Effects of plant growth-promoting bacteria on the performance of chickpea seedlings - CÂNDIDO, Ruan da Silva; SILVA, Patrícia Costa; DELMOND, Josué Gomes; GIONGO, Pedro Rogerio; COUTO, Eduardo Silva; SILVA, Lucas Inácio da; FERREIRA, Ana Flávia Alves; ARAÚJO, Emanuelly Silva; VALÉRIO, Carlos Miguel Barbosa; COSTA, Adriana Rodolfo da (Food Science and Technology, 2025)
Using plant growth-promoting bacteria (PGPB) is a sustainable option for the cultivation of chickpeas as well as other crops, and their effects can be observed from the beginning of development. The objective of this study was to evaluate the development of the seedlings of chickpea cultivars under inoculation with PGPB. The experiment was conducted in a greenhouse, and the experimental design adopted was completely randomized in a 2 × 3 factorial scheme (2: application or not of the inoculant in chickpea seed treatment; 3 chickpea cultivars: BRS Aleppo, BRS Cícero, and BRS Toro). In this research, it was observed that growth-promoting bacteria showed positive effects in the first days of chickpea development, having a more significant effect on the growth and accumulation of root mass. The authors suggested that biomass accumulation in the root system is due to the secretion of substances by microorganisms inoculated via seeds, which promote root development and consequently greater absorption of nutrients. The BRS Aleppo cultivar showed better performance in terms of seedling emergence, but the seedlings had lower biomass accumulation in both shoots and roots. The use of PGPB promoted fast and early chickpea growth.